Os clíticos pronominais em contextos de reflexividade/pronominalidade verbal na fala da cidade de Catalão-GO. - Sirlene Antonia Rodrigues Costa (2022)
This doctoral thesis shows the results and considerations about the studies on the variation and changing of the clitic pronouns me, te, se e nos, in contexts where the Brazilian Portuguese verbs indicate a sense of reflexivity and pronominality. To do so, speech samples from the city of Catalão-GO were analysed based on the Varationist Sociolinguistic’ theoretical and methodological assumptions and also based on the Variation Theories and Linguistics Changings. The linguistics analysis had the dependent binary variety as reference: presence x absence of clitic pronouns, in the specified verbal contexts, considering these variable alternation in the catalanos speech, it is influenced by linguistic and social factors. Therefore, the main objectives consisted in the analysis of the clitic pronoun structure analysis, beginning with the variables of presence x absence of these clitics, in sentences where its main verbs are characterized by the reflexive/pronominal, having as reference the speech in the city of Catalão-GO. Among the specific objectives, the research had as a goal to identify whether the absence of the pronominal clitics, in these verbal contexts, it is characterized by a linguistic variation or if it can already be considered as a linguistic change. Besides, we aimed at verifying, in quantitative and qualitative terms, the possible interferences of the independent variables on the dependent variables. Therefore, the data was submitted to the Statistic Program GoldVarb X which generated results that made it possible to proceed on the linguistic analysis, represented in graphics and charts interpreted on the light of theories. These analyses appeared in 511 verbal occurrences, in a total of 133 different verbs, obtained from the interviews with 24 interviewees, 12 men and 12 women. The informants were grouped in three schooling levels (low, middle and high) and in three different age groups (young = 18 to 29 years old, adults = 30 to 49 and adults+ = above 50). It is realized that the results indicated that there is and advanced linguistic change in Catalão-GO, favoring the absence of the clitic pronouns, also observed in other regions in the state of Goiás. Besides, the numbers also showed that the school has a strong influence on the preservation of the general rule that asks for the presence of clitics on these specified verbal contexts. However, even among the most schooled speakers it is verified that changes also occur, although this happens more slowly and less expressively.